Results in the ESPN/ERA-EDTA Registry suggest disparities in access to kidney transplantation but little variation in graft survival of children across Europe - Bonthuis, Marjolein; Tönshoff, Burkhard (Kidney international, 2020)
One of the main objectives of the European health policy framework is to ensure equitable access to high-quality health services across Europe. Here we examined country-specific kidney transplantation and graft failure rates in children and explore their country- and patient-level determinants. Patients under 20 years of age initiating kidney replacement therapy from January 2007 through December 2015 in 37 European countries participating in the ESPN/ERA-EDTA Registry were included in the analyses. Countries were categorized as low-, middle-, and high-income based on gross domestic product. At five years of follow-up, 4326 of 6909 children on kidney replacement therapy received their first kidney transplant. Overall median time from kidney replacement therapy start to first kidney transplantation was 1.4 (inter quartile range 0.3-4.3) years. The five-year kidney transplantation probability was 48.8% (95% confidence interval: 45.9-51.7%) in low-income, 76.3% (72.8-79.5%) in middle-income and 92.3% (91.0-93.4%) in high-income countries and was strongly associated with macro-economic factors. Gross domestic product alone explained 67% of the international variation in transplantation rates. Compared with high-income countries, kidney transplantation was 76% less likely to be performed in low-income and 58% less likely in middle-income countries. Overall five-year graft survival in Europe was 88% and showed little variation across countries. Thus, despite large disparities transplantation access across Europe, graft failure rates were relatively similar. Hence, graft survival in low-risk transplant recipients from lower-income countries seems as good as graft survival among all (low-, medium-, and high-risk) graft recipients from high-income countries.